Poetry of The Lamiyyat ‘Arabs in The Science of Balaghah | al Shier Lamiyyat al ‘Arab Fii ‘Ilm al Balaghah: الشعر لامية العرب فى علم البلاغة (دراسة بيانية تحليلية) - Barakat Mohamed Ahmed (Mantiqu Tayr: Journal of Arabic Language, 2022)
This study deals with the Arab Lamiyyat, which is derived from ancient poetry, as it represents the pre-Islamic environment and the homeless environment in particular. Literature is represented in all stanzas of the poem, the letter to Roy is the best guide, for one of the letters of arrogance denotes activity in speech, and eloquence in listening, the repetition of violent metonymy in his poetry. This type of research is a type of qualitative research. The working procedure of this research method is to describe the existing data according to the context, which means, this research only requires the text of the literary works in it, as well as the theories used in this study. The approach in this study is an objective approach which focuses on literary texts and the theory used in the form of the study of Balaghah science. The researcher recommends general and specific rhetorical applied studies, starting with the Qur'an, the sacred Sunnah, the eyes of Arabic poetry and the rest of the llamas against poetry and others.